Clinical Features, Management, and Outcomes of Chest Trauma at a Tertiary-Care Centre in India: A Retrospective Observational Study - Bhupinder Singh Walia (Hindawi Limited, 2021)
Introduction. Chest is one of the main sites of injuries in trauma being a part of the torso. Many important organs lie in rib cage. However, data on chest injuries are scarce. Methods. A retrospective study was carried out for chest trauma patients including polytrauma (n = 184) from hospital records for five years (2016–2020). Various parameters including demographic profile, mode of injury, management, and outcomes were studied. Results. Mean age of patients was 37 ± 16 years with a male to female ratio of 2.4 : 1. Road traffic injuries remained the most common cause of trauma followed by assaults. Most of the patients were managed conservatively (55.43%). Mortality was seen in only 1.63% patients. Conclusion. Young male patients are usually affected by trauma. Road traffic injuries are the commonest cause. However, most patients can be managed by conservative treatment and mortality is seen only in polytrauma patients in the present study.